Kebijakan Hukum di Eropa Tentang Konsep Sekularisme Atau Laicite di Prancis - Hissah Kristina Marbun; Rohma Safitri; Rinnauli Saragih; Amelia Situmorang; Isnaniah Isnaniah; Sri Hadiningrum (International Forum of Researchers and Lecturers, 2024)
This article aims to examine the principle of French religion being secular, or laïcité. France adopted this principle in 1905. This principle separates religious and state affairs, including state interference in religious worship. This principle also aims to protect the freedom of French people to adhere to or not adhere to religion and prevent religion from entering state institutions, one of which is education. The method used in this research is library research, namely a method of collecting data by understanding and studying theories from various literature related to the research.